SOEP-Metafile.do - A Stata do-file to generate a metafile for the SOEP data files - Klaudia Erhardt (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This paper presents the Stata do-file SOEP-Metafile.do (version for SOEP-Users). The do-file is used to generate a summary file (metafile) of the SOEP data. To execute SOEP-Metafile.do in their local environment, users have to make only a few adjustments to the path definitions and options. Apart from this, the generation of a metafile with SOEP-Metafile.do is completely automated.
doi:10.5281/zenodo.1256001
Keywords: 330